2014
DOI: 10.1007/s12010-014-1206-6
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Peptidoglycan-Specific Aptamers for Bacterial Cells Identification

Abstract: Peptidoglycan is a highly complex and essential macromolecule of bacterial outer cell wall; it is a heteropolymer made up of linear glycan strands cross-linked by peptides. Peptidoglycan has a particular composition which makes it a possible target for specific bacterial recognition. Aptamers are single-stranded DNA or RNA oligonucleotides that bind to target molecules with high affinity and specificity. Aptamers can be labeled with different radioisotopes and possess several properties that make them suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Two peptidoglycan-targeting DNA aptamers have also been identified that displayed high affinities towards Staphylococcus aureus cells. 160 The dissociation constants of the two aptamers towards peptidoglycan were 0.415 mM and 1.261 mM. It was observed that the aptamers had similar binding to both Gram negative and Gram positive bacterial cells, despite the latter typically consisting of a higher content of and more exposed peptidoglycan.…”
Section: Aptamersmentioning
confidence: 96%
“…Two peptidoglycan-targeting DNA aptamers have also been identified that displayed high affinities towards Staphylococcus aureus cells. 160 The dissociation constants of the two aptamers towards peptidoglycan were 0.415 mM and 1.261 mM. It was observed that the aptamers had similar binding to both Gram negative and Gram positive bacterial cells, despite the latter typically consisting of a higher content of and more exposed peptidoglycan.…”
Section: Aptamersmentioning
confidence: 96%
“…The synthesis of macromolecular peptidoglycan, a cell wall component that is present in both Gram-positive and Gram-negative bacteria, is another target for the specific imaging of bacterial infections. A single-stranded oligonucleotide [117], able to bind peptidoglycans with high specificity and sensitivity [118], was labelled with different radioisotopes and as such can be used for imaging bacterial and fungal infections [119,120]. Imaging studies with the 99m Tc-aptamer were carried out in thigh muscles of mice either infected with S. aureus, C. albicans, or with a sterile inflammation.…”
Section: Imaging Carbohydrate Metabolismmentioning
confidence: 99%
“…Therefore, several ssDNA aptamers have been developed against staphylococcal enterotoxins (SEs). To develop potential diagnostic agents, aptamer APT SEB1 for staphylococcal enterotoxin B (SEB), 42 aptamer C10 for S. aureus enterotoxin C1 (SEC1), 43 aptamer R12.06 for α-toxin, 44 aptamer Antibac1 and Antibac2 for a peptidoglycan 45 and aptamer PA#2/8 for protein A 46 were generated for the detection of SEs. Among these aptamers, aptamer R12.06 for αtoxin was utilized in a modified sandwich ELISA and sensitive detection of 200 nM a-toxin in undiluted human serum samples was achieved.…”
Section: S Aureusmentioning
confidence: 99%